Children and Young People's Improving Access to Psychological Therapies: inspiring innovation or more of the same?†. (April 2015) - Timimi, Sami
Summary: In 2007 the UK Government announced a substantial expansion of funding for psychological therapies for those presenting with common mental health problems. This 'Improving Access to Psychological Therapies' (IAPT) project was widely welcomed, however, evidence backed, economic, and conceptual critiques were voiced from the start and the project remains controversial. In 2011, the UK government announced it was extending the IAPT project to encompass services for children and young people with the aim of 'transforming' the way mental health services are delivered to them. Here I critically reflect on the problems associated first with IAPT and then with CYP-IAPT and ponder whether CYP-IAPT is significantly different to the problematic adult IAPT project or more of the same.